Przyszłość globalnej ekonomii na stokach Gstaad. Codzienność Institut Le Rosey - szwajcarskiej elitarnej szkoły średniej - Gromkowska-Melosik, Agnieszka (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This text is dedicated to the Swiss elite secondary school, which prepare young people from very wealthy families to function in the environment of the global elite. This is boarding school, tending to a very high degree of internationalization, offering luxurious living conditions and education. The cost of staying in it are very high and significantly exceed those that are incurred in connection with training in the most prestigious universities. In this school, we have to deal with the construction of a global, multicultural, corporate identity that can adapt to any market conditions. This school is characterized by the international composition of the students, there is a focus on not exceeding any nation in the percentage of the total student population. The motto of Institut Le Rosey refers to – exposed often in the context of Switzerland – the category of „correctness” or perfection.
Keywords: edukacja; elitarność; globalizacja; internat; wielokulturowość